DAMPAK KUALITAS PRODUK, HARGA DAN WORD OF MOUTH TERHADAP MINAT BELI KONSUMEN PADA UD CATUR PUTRA DI MENGWI BADUNG - Made Setena; Ni Putu Sri Mariyatni; Ni Made Rai Juniariani (Fakultas Ekonomi Universitas Warmadewa, 2022)
The purpose of this study was to examine the impact of product quality, price and word of mouth on consumer purchasing power at UD Catur Putra in Mengwi Badung. Marketing is the key to success of a business organization. Marketing management in era 4.0 besides being able to a competitor, is also capable of being an innovator able to adapt to available technological advances so that promotions related to the products offered besides being offline can also be done online (via social media). UD Catur Putra which is enganged in the production of Balinese gamelan has an obligation to meet consumer buying interest. The factors that can influence consumer buying interest are: product quality, price, and word of mouth. The results of multiple linear regression analysis show a positive direction between product quality, price and word of mouth on consumer buying interest. Thus, it can be stated that the level of consumer buying interest is influenced jointly by product quality, price and word of mouth. The F-test is a test of the significance of multiple linear regression coefficients obtained by F-count 18,151 > F-table 3,093 indicating that it is true that there is a simultaneous significant effect between product quality, price and word of mouth on consumer buying interest. Significance test using t-test the obtained t-count values for variables are 2.381, 2.268 and 3.729 > t-table 1.661 indicating that it is true that there is a significant positive influence individually between product quality, price and word of mouth on consumer buying interest.